Spinel chemistry from Madawara Mafic-Ultramafic Complex, Lalitpur District, Uttar Pradesh, India (Journal of Nepal Geological Society, 2019)
Spinel in peridotite of the Pipariya area in Madawara Mafic and Ultramafic Complex (MMUMC) occur as euhedral to subhedral inclusion within the silicates. They exhibit regular to irregular shape and is altered to ferritchromite to magnetite along the cracks and boundaries. Cr-spinel is characterised by high values of Cr# (79.7-98.4) and low Mg# and Al# values (i.e., 20.41-9.66 and 0.49- 17.71, respectively) and are identified as Fe-chromite. Chemical discontinuity/zones between the core and rim can be observed in the analysed grain. The textural and chemical features of investigated suggest low- to sub greenschist facies metamorphism consistent with the estimated metamorphic equilibrium temperature of 500°C-550°C.Mineral chemistry of these spinel suggests that spinel in peridotite of Pipariya in the Madawara Mafic and Ultramafic Complex depicts that these Cr-spinel may have been derived from boninitic related magmas at arc to suprasubduction zone tectonic setting at low degree of partial melting.